Islamic learning portfolio assessment at islamic senior high school - Supriyadi, Supriyadi; In’ami, Moh; Tobroni, Tobroni; Astutik, Anita Puji (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Islamic education plays a crucial role in shaping the character and faith of young Muslims.This study aims to understand portfolio assessment on Islamic religious learning in Islamic Senior High School after Covid-19 as an alternative to developing an authentic and holistic student portfolio assessment implementation model. Researchers analyze related to the implementation of portfolio assessments in Islamic religious learning conducted by Islamic religious teachers, and academic supervisors in Islamic Senior High School. This research uses qualitative research methods with a type of case study research with a constructivism paradigm. This study shows that the implementation of portfolio assessment in Islamic religious learning is carried out by organizing the assessment of the indicator stage, and the assessment of the artifact stage. Several problems were found in the implementation of portfolio assessment, namely (1) the formative indicator assessment stage; (2) the programmatic task assessment indicator stage; (3) the indicator stage of assessment of supporting activities; (4) the stage of attitude and personality assessment indicators; (5) the collection stage of the work; (6) the selection stage of the work; (7) the reflection stage of the work; (8) the exhibition stage (connection) of students' work, and (9) the problem of general aspects related to Madrasah management.Thus, portfolio assessment should interact with the learning process, both at the beginning and at the end of the assessment.